Repensando a adoção de normas de coordenação dos processos de insolvência com conexão internacional no Brasil - Moraes, Leonardo Theon de (2017)
This paper analyzes the evolution of the treatment given to international insolvencies processes in Brazil, the various mechanisms of international cooperation that have been created in order to promote a more reasonable and economically efficient system of international bankruptcy cases for the collection and distribution of assets also demonstrate the need to adapt the models of coordination of insolvency procedures with international connection to the underdeveloped and developing countries. Thus, in the first chapter of this article is dealt the urgency and relevance of the debate involving the adoption of norms for the coordination of insolvency processes with international connection in Brazil. Then, in Chapter 2 sets out the principles applicable to International Insolvency Law and the main models of international cooperation in insolvency proceedings with international connection. Then, in the third chapter, the history and treatment of international insolvency law in Brazil, by analyzing the current and applicable national laws and by analyzing the largest case of judicial recovery (bankruptcy protection) of the country - the case of the OGX Group. Finally, it is pointed out the national trend towards the adoption of a universalist model for the coordination of international insolvency proceedings with connection in Brazil, dealing with the Draft Laws in process before the Federal Senate and the Chamber of Deputies, being, finally, exposed The main issues in the ipsis literis adoption of a universalist model by an underdeveloped country. This article seeks to demonstrate, the need to adapt the models of insolcency procedures with international connection to the underdeveloped and developing countries, and the need Brazil to create norms for the coordination of judicial recoveries and transnational bankruptcies that are aligned with the Constitutional task of transforming economic structures to overcome underdevelopment. The importance of this article in the corporate world is to provide greater stability and legal security between the commercial relations of the countries, providing the increase of their economic relations and taking care of the new aspects of the market, globalization and the modern world.